Dual Career through the Analysis of Policy Documents: A Case Study Focusing on Athletics - Olah, David; Nyisztor, Petra; Borbely, Szilvia; Bognar, Jozsef (Central European Journal of Educational Research, 2022)
Careers can be influenced by several factor groups: opportunities provided by (1) the environment, (2) ambition, and (3) personal aptitude (Juhász & Matiscsákné Lizák, 2014). In the case of a dual career in sports, an athlete’s career is not limited to sports only, but also can include education. It is worthwhile for sportsmen to learn alongside their athletic career. For, a sporting career can come to an end at any time due to any unexpected event (Baráth et al., 2014). This dual career’s success depends heavily on the people in the athlete’s immediate environment. In our research, we used a qualitative method to conduct a content analysis of policy documents and semi-structured interviews with Olympians of three countries, one from Slovenia, one from Germany, and one from Hungary. We divided up our investigation into questions related to funding, professional background and studies. Their opinions showed that all three athletes are satisfied with the support they receive for their current dual careers, with only the Slovenian athlete feeling a slight deficiency. They have successfully combined their studies and sport, and all three have attended or are currently attending higher education. It can be concluded that all sport policy efforts show the potential for dual career assistance with a focus on self-efficacy. No differences can be found in the expectations of these elite athletes, and all feel the need to continue their studies in addition to sporting, regardless of whether or not it coincides with their previous studies. As regards the need to continue studying, the Slovenian athlete felt the least need. This degree of “need” does not affect the performance of the athletes in their respective sports, as all of them love sports. All receive adequate funding as well. In all three countries studied, we found such a level of support for the athlete that ought to be held up as ‘good practice’. The German competitor in particular possesses such professional staff that we would highlight and recommend it as good practice to follow.